P217 Does chemotherapy increase the risk of developing pleural infections in patients with indwelling pleural catheters?. (14th November 2013) - Edwards, H; Bishop, LJ
Abstract : Introduction: Indwelling Pleural Catheters (IPC) are indicated for the management of recurrent or resistant Malignant Pleural Effusions (MPE), usually after talc pleurodesis. While generally safe and effective, they carry a risk of pleural infection thought to be 4.7%[1]. We have noticed a number of empyema's in patients receiving chemotherapy with an IPC, and want to see if there is an increased risk for IPC associated infection with chemotherapy in MPE above that in the general population. Methods: We reviewed all patients in our hospital who have received an indwelling pleural catheter, from the implementation of the service in February 2011 until June 2013. We reviewed patient details, indication for IPC, possible or definite infection post procedure and relation to chemotherapy. This information was obtained from patients' medical records, pathology reports and the radiology system. Results: 86 IPC's have been inserted from February 2011 until June 2013. Five of these were replacement drains (replaced due to blockage, displacement or infection). A total of 21/86 (24%) patients had chemotherapy either immediately before IPC insertion or with IPC in place. 11 patients (12.8%) were treated for suspected pleural infections, but only 5 patients (5.8%) were confirmed with positive pleural cultures. 3 of the 5 patients were undergoing chemotherapy at the time of the infection Conclusions: Patients receiving indwelling pleural catheters are usually those with a malignant process and therefore chemotherapy is a common treatment used in this population. Although our numbers are small, they suggest that there may be an increased risk of pleural infection in patients with an IPC who undergo chemotherapy. Until a larger analysis can be done, it would be reasonable to consider prophylactic antibiotics during catheter insertion if a patient is due to have chemotherapy. References: Fysh ET et al . Clinical Outcomes of Indwelling Pleural Catheter-Related Pleural Infections: an international multicenter study. Chest . 2013 Jul 4